Pengaruh Stres Kerja, Pengembangan Karir dan Kepribadian terhadap Komitmen Organisasional: Studi pada RSUD Dr. Gondo Suwarno Ungaran Kabupaten Semarang - Safrizal Rizky Surya Chandra; Tristiana Rijanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to analyze the influence of work stress, career development and personality on organizational commitment at RSUD Dr. Gondo Suwarno Ungaran, Semarang Regency. The type of data used is primary data, namely data obtained directly from original sources in the form of questionnaires. The population of this study were employees at RSUD Dr. Gondo Suwarno Ungaran. Sampling was carried out using a purposive sampling technique, namely a sampling technique using certain criteria, so that a sample of 315 respondents was obtained. The data collected was analyzed using factor analysis to test the validity of the question items, test reliability using Cronbach Alpha, and test hypotheses using multiple linear regression. The research results show that the work stress variable has no effect on organizational commitment, the career development variable has a positive and significant effect on organizational commitment, and the personality variable has a positive and significant effect on organizational commitment.